Dual antibiotic prevention bundle is associated with decreased surgical site infections. Issue 9 (September 2020) - Kuznicki, Michelle; Mallen, Adrianne; McClung, Emily Clair; Robertson, Sharon E; Todd, Sarah; Boulware, David; Martin, Stacy; Quilitz, Rod; Vargas, Roberto J; Apte, Sachin M
ABSTRACT : Background : Gynecologic oncology surgery is associated with a wide variation in surgical site infection risk. The optimal method for infection prevention in this heterogeneous population remains uncertain. Study Design : A retrospective cohort study was performed to compare surgical site infection rates for patients undergoing hysterectomy over a 1‐year period surrounding the implementation of an institutional infection prevention bundle. The bundle comprised pre‐operative, intra‐operative, and post‐operative interventions including a dual‐agent antibiotic surgical prophylaxis with cefazolin and metronidazole. Cohorts consisted of patients undergoing surgery during the 6 months prior to this intervention (pre‐bundle) versus those undergoing surgery during the 6 months following the intervention (post‐bundle). Secondary outcomes included length of stay, readmission rates, compliance measures, and infection microbiology. Data were compared with pre‐specified one‐sided exact test, Chi‐square test, Fisher's exact test, or Kruskal‐Wallis test as appropriate. Results : A total of 358 patients were included (178 PRE, 180 POST). Median age was 58 (range 23‐90) years. The post‐bundle cohort had a 58% reduction in surgical site infection rate, 3.3% POST vs 7.9% PRE (−4.5%, 95% CI −9.3% to −0.2%, p=0.049) as well as reductions in organ space infection, 0.6% POST vs 4.5% PRE (−3.9%, 95% CI −7.2% to −0.7%, p=0.019), and readmission rates, 2.2% POST vs 6.7% PRE (−4.5%, 95% CI −8.7% to −0.2%, p=0.04). Gram‐positive, Gram‐negative, and anaerobic bacteria were all prevalent in surgical site infection cultures. There were no monomicrobial infections in post‐cohort cultures (0% POST vs 58% PRE, p=0.04). No infections contained methicillin‐resistant Staphylococcus aureus . Conclusion : Implementation of a dual antibiotic infection prevention bundle was associated with a 58% reduction in surgical site infection rate after hysterectomy in a surgically diverse gynecologic oncology practice.